Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4085/1062-6050-45.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Collagen Expression, and Anterior Cruciate Ligament Strength in Rats

Abstract: Context: Sex-specific responses to steroid sex hormones have been suggested as a potential cause for the disparate anterior cruciate ligament (ACL) injury rates between male and female athletes. Type 1 collagen (T1C) and type 3 collagen (T3C) are crucial structural components that define the ligament's ability to withstand tensile loads. Messenger RNA (mRNA) is an important mediator of downstream collagen synthesis and remodeling, but the sex-specific mechanisms of collagen mRNA expression and ACL strength are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…After the application of a 1-N preload, specimens were preconditioned for 10 cycles from 0 to 0.5 mm at a rate of 0.25 mm/s. 31,32 The specimens were allowed to recover at zero displacement for 30 seconds before being loaded to failure at 0.25 mm/s. Data were recorded at 20 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…After the application of a 1-N preload, specimens were preconditioned for 10 cycles from 0 to 0.5 mm at a rate of 0.25 mm/s. 31,32 The specimens were allowed to recover at zero displacement for 30 seconds before being loaded to failure at 0.25 mm/s. Data were recorded at 20 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…In athletic training, examples of very traditional bench research can be found in the literature, such as animal studies examining collagen expression in the anterior cruciate ligament. 15 Promising bench research findings should first be translated into bedside studies that involve actual patient populations. Within the context of athletic training research, the term bedside research is equivalent to the majority of patient-based therapeutic studies that are conducted within research laboratories.…”
Section: Translational Continuummentioning
confidence: 99%